Terra, espírito e homem: a nova capital e as imagens da branquitude na revista Brasília - Amanda Alves Sicca Lopes (2021)
The construction of Brasília was, between many things, within the ideal constructed by the hegemonic narratives, the ripeness of the Brazilian nation, as well as the affirmation of the genius of its people, seeking the renewal of its identity in order to place Brazil between the great nations of the western civilization. Although dressed with so many significations that had the objective of enhancing the country’s image, Brasília was also the continuation of the colonization started in 1500. Although today this issue is rarely called upon when referring to the construction of the capital, this was a fundamental argument for its realization. The territorial occupation is essential for colonization, since, in addition to the material domain, it also expresses the expansion of a subjective domain that sustains the social form of the colonizer in the invaded territory. This structure, essentially racist, places in what we call whiteness the privilege over the accesses not only of the material reality, but also of the symbolic ones, creating a world where those who are racially identified as white are at advantage over those who aren’t. The studies on this issue are relatively recent in the Brazilian academic arena, very few attempt to trace the relationship between these subjectivities and their territorial occupation, especially their connection with the process of colonization of this territory. Therefore, this work seeks to understand the construction of the whiteness starting from Brasília, which was fundamental for the expansion of its subjectivation modes throughout the Brazilian territory, analyzing the discourse of the first 44 Revistas brasília, which were created by Novacap with the purpose of promoting the construction of the new capital. Taking into account the rich material that are these magazines, the approach followed three main perspectives: the narrativies about the land, about the spirit – the sensitive world – and about the man, seeking primarily to understand which beliefs supported and which led to the expansion of the subjectivation mode that sustains the so-called Brazilian civilization. The work also sought to deepen the understanding of the discourses of the colonization in the 20th century, little related to the construction and expansion of the socio-spatial model that manifests itself in the material reality of the national territory.